Revisiting Preclinical Observations of Several Histamine H3 Receptor Antagonists/Inverse Agonists in Cognitive Impairment, Anxiety, Depression, and Sleep–Wake Cycle Disorder - Alhusaini, Mera; Eissa, Nermin; Saad, Ali K.; Beiram, Rami; Sadek, Bassem (Frontiers in Pharmacology, 2022)
A relationship appears to exist between dysfunction of brain histamine (HA) and various neuropsychiatric brain disorders. The possible involvement of brain HA in neuropathology has gained attention recently, and its role in many (patho)physiological brain functions including memory, cognition, and sleep–wake cycle paved the way for further research on the etiology of several brain disorders. Histamine H3 receptor (H3R) evidenced in the brains of rodents and humans remains of special interest, given its unique position as a pre- and postsynaptic receptor, controlling the synthesis and release of HA as well as different other neurotransmitters in different brain regions, respectively. Despite several disappointing outcomes for several H3R antagonists/inverse agonists in clinical studies addressing their effectiveness in Alzheimer’s disease (AD), Parkinson’s disease (PD), and schizophrenia (SCH), numerous H3R antagonists/inverse agonists showed great potentials in modulating memory and cognition, mood, and sleep–wake cycle, thus suggesting its potential role in neurocognitive and neurodegenerative diseases such as AD, PD, SCH, narcolepsy, and major depression in preclinical rodent models. In this review, we present preclinical applications of selected H3R antagonists/inverse agonists and their pharmacological effects on cognitive impairment, anxiety, depression, and sleep–wake cycle disorders. Collectively, the current review highlights the behavioral impact of developments of H3R antagonists/inverse agonists, aiming to further encourage researchers in the preclinical drug development field to profile the potential therapeutic role of novel antagonists/inverse agonists targeting histamine H3Rs.